Absence of Protoheme IX Farnesyltransferase CtaB Causes Virulence Attenuation but Enhances Pigment Production and Persister Survival in MRSA - Xu, Tao; Han, Jian; Zhang, Jia; Chen, Jiazhen; Wu, Nan; Zhang, Wenhong; Zhang, Ying (Frontiers in Microbiology, 2016)
The membrane protein CtaB in S. aureus is a protoheme IX farnesyltransferase, involved in the synthesis of the heme containing terminal oxidases of bacterial respiratory chain. In this study, to assess the role of CtaB in S. aureus virulence, pigment production, and persister formation, we constructed a ctaB mutant in the methicillin-resistant Staphylococcus aureus (MRSA) strain USA500. and We found that deletion of ctaB attenuated growth and virulence in mice but enhanced pigment production and formation of quinolone tolerant persister cells in stationary phase. RNA-seq analysis showed that deletion of ctaB caused decreased transcription of several virulence genes including RNAIII which is consistent with its virulence attenuation. In addition, transcription of 20 ribosomal genes and 24 genes involved in amino acid biosynthesis was significantly down-regulated in the ctaB knockout mutant compared with the parent strain. These findings suggest the importance of heme biosynthesis in virulence and persister formation of S. aureus.